Photo-induced disinfection property and photocatalytic activity based on the synergistic catalytic technique of Ag doped TiO2 nanofibers - Wu, Ming-Chung; Lin, Ting-Han; Hsu, Kai-Hsiang; Hsu, Jen-Fu (Applied surface science, 2019)
Various metal-doped TiO2 nanofibers were prepared by hydrothermal synthesis followed by the thermal treatment in air. An array of metal dopants including Ag, Au, Co, Cr, Cu, Fe, Ni, Pd, Pt, Y, and Zn, were respectively doped into TiO2 NFs to acquire the visible-light photocatalytic activity. Considering the photodegradation results under visible-light illumination, Ag doped TiO2 NFs was chosen to study further. Then, the optimal doping level and calcination process were studied systemically to obtain the highly visible light active Ag doped TiO2 NFs. As the Ag doping concentration increased up to 5.00 mol%, anatase to rutile phase transition was observed. Meanwhile, based on the consistent results of synchrotron X-ray spectra, element analysis, and morphological observation, Ag2O was detected and located on the surface of as-synthesized Ag doped TiO2 NFs. Thus, the photodegradation of methyl orange by using 5.00 mol%-Ag doped TiO2 NFs calcined at 600 °C performed the highest visible-light photodegradation activity. Moreover, it also showed the excellent disinfection against E. coli and S. aureus under visible light due to the synergistic effect of Ag2O and photo-induced reactive oxygen species (ROS) formed by TiO2 photocatalyst. The synthesized Ag doped TiO2 NFs makes large-scale and convenient fabrication possible, and it has tremendous practical potentials in the photodegradation of environmental pollution and disinfects bacteria behavior. [Display omitted] •Ag-TiO2 NFs is synthesized by a single-step hydrothermal method.•Ag dopant promotes the phase transform to rutile/anatase mixing phase.•Ag2O precipitates on TiO2 surface as doping concentration up to 5.00 mol%.•Ag-doped TiO2 NFs shows great disinfection activity against E. coli and S. aureus.•Ag2O and photo-induced ROS contribute to the synergistic effect on disinfection.